ROLE OF TEA DREGS LIQUID ORGANIC FERTILIZER AND PLANT MEDIA COMPOSITION IN INCREASING TOMATO RESULTS (Lycopersicon esculentum Mill.) - Maryana, Maryana; Haryanto, Darban; Lifia, Reti Columba (Journal TECHNO, 2023)
The aim of this study was to determine the composition of the tea waste liquid organic fertilizer and the composition of the growing media in increasing the yield of tomato plants. The research was conducted from June to November 2022 at the Wedomartani Experimental Garden, Faculty of Agriculture UPN "Veteran" Yogyakarta Kapanewon Ngemplak, Sleman Regency, Yogyakarta. Research method with polybags using factorial (3 × 3 + 1) arranged in a completely randomized design. The first factor was tea waste liquid organic fertilizer with 3 levels: 200 ml/l, 300 ml/l, and 400 ml/l. The second factor was the composition of the planting medium in the form of a mixture of soil and goat manure consisting of 3 levels: (1:1), (1:2), and (2:1). For each treatment of tea waste liquid organic fertilizer, 3 grams of NPK 16:16:16 fertilizer was added. The control treatment used soil and 3 grams of NPK fertilizer for each application of fertilization which was given 3 times. The results showed that the combination of treatments was better than the control on tomato fruit diameter per harvest, tomato fresh fruit weight per third and fourth harvest. There was no interaction between the concentration of tea waste liquid organic fertilizer and the composition of the planting medium. Concentration of 400 ml/l tea waste liquid organic fertilizer gave higher yields on tomato fruit diameter per harvest, tomato fresh fruit weight per harvest and total tomato fresh fruit weight. The composition of the growing media with a composition of 1:1 gave the highest yield on tomato fruit diameter per harvest and a composition of 2:1 for total fresh fruit weight of tomatoes.